Modification of Fibronectin by Non-Enzymatic Glycation Impairs K+ Channel Function in Rat Cerebral Artery Smooth Muscle Cells - Yang, Yan; Nourian, Zahra; Li, Min; Sun, Zhe; Zhang, Liping; Davis, Michael J.; Meininger, Gerald A.; Wu, Jianbo; Braun, Andrew P.; Hill, Michael A. (Frontiers in Physiology, 2022)
Fibronectin (FN) enhances K+ channel activity by integrin-mediated mechanisms. As vascular smooth muscle (VSM) K+ channels mediate vasodilation, we hypothesized that modification of fibronectin, via advanced non-enzymatic glycation, would alter signaling of this extracellular matrix protein through these channels. Bovine FN (1mg/ml) was glycated (gFN) for 5 days using methylglyoxal (50mM), and albumin was similarly glycated as a non-matrix protein control. VSM cells were isolated from rat cerebral arteries for measurement of macroscopic K+ channel activity using whole cell patch clamp methodology. Pharmacological inhibitors, iberiotoxin (0.1 M) and 4-aminopyridine (1 mM), were used to identify contributions of large-conductance, Ca2+-activated, K+ channels and voltage-gated K+ channels, respectively. Compared with baseline, native FN enhanced whole cell K+ current in a concentration-dependent manner, whereas gFN inhibited basal current. Furthermore, native albumin did not enhance basal K+ current, but the glycated form (gAlb) caused inhibition. gFN was shown to impair both the Kv and BKCa components of total macroscopic K+ current. Anti-integrin 5 and 1 antibodies attenuated the effects of both FN and gFN on macroscopic K+ current at +70 mV. Consistent with an action on BKCa activity, gFN decreased the frequency of spontaneous outward currents (STOCs) while gAlb inhibited whole cell K+ current predominantly through Kv, showing little effect on STOCs. A function-blocking, anti-RAGE antibody partially reversed the inhibitory effects of gFN, suggesting involvement of this receptor. Further, gFN caused production of reactive oxygen species (ROS) by isolated VSMCs as revealed by the fluorescent indicator, DHE. ROS production was attenuated by the RAGE blocking antibody. Collectively, these studies identify ion channel-related mechanisms (integrin and ROS-mediated) by which protein glycation may modify VSMC function.